The molecular binding interactions of inhibitors and activators of phosphoenolpyruvate carboxylase - Mancera, Ricardo; Carrington, B. (Elsevier, 2005)
We have performed molecular modelling studies of the binding to maize phosphoenolpyruvate carboxylase (PEPC) of phosphoenolpyruvate (PEP) and a number of representative competitive inhibitors. We predict that all these compounds share a common binding mode and that the differences in inhibitory activity of the various inhibitors arise mainly from either increased hydrophobic interactions of cis substituents or small but significant changes in their binding mode arising from steric clashes of trans substituents with the active site. We have also performed molecular modelling studies of glucose-6-phosphate (G6P) and a number of other allosteric activators in their putative allosteric binding site in this enzyme. We predict that these molecules share the same binding mode for their phosphate moiety while some of them engage in a variety of hydrogen bonding interactions with residues from different subunits of the enzyme, and others establish hydrophobic and van der Waals interactions with other regions of the allosteric binding site.